Late-onset sepsis in newborns caused by Bacillus Cereus: a case report and literature review - Wang Zhang; Caihua Ma; Linghui Hu; Ling Wang; Falin Xu (BMC, 2024)
Abstract Bacillus cereus is a bacterium capable of causing late-onset neonatal sepsis. By analyzing 11 cases, this study investigates the diagnosis, treatment, and prognosis of Bacillus cereus infections, aiming to provide insights into clinical diagnosis and therapy. The study scrutinized 11 instances of late-onset neonatal sepsis, including two fatalities attributable to Bacillus cereus, one accompanied by cerebral hemorrhage. An examination and analysis of these cases' symptoms, signs, laboratory tests, and treatment processes, along with a review of related literature from 2010 to 2020, revealed a high mortality rate of 41.38% in non-gastrointestinal infections caused by Bacillus cereus. Our findings underscore the critical importance of rapid diagnosis and effective antimicrobial therapy in reducing mortality rates. Once the source of infection is identified, implementing effective infection control measures is essential.